ΝΗΣΑΙ IN SOPHOCLES, FR. 439 R. (December 2015) - Olson, S. Douglas
Abstract : πέπλους τε νῆσαι λινογενεῖς τ' ἐπενδύτας τε νῆσαι Canter : τε νίσαι Poll. A : τάνυσαι Poll. FS nêsai mantles and outer garments born of flax Greek has three verbs νέω: (A) 'swim', (B) 'spin' and (C) 'heap up, pile'. The aorist infinitive of both (B) and (C) is νῆσαι. LSJ (followed by Ellendt) takes Sophocles, fr. 439 R. (from Nausicaa or Washing-women ) to be an instance of νέω (B). Pearson comments: 'νῆσαι is loosely used for ὑϕαίνειν. The process of spinning, being preparatory to that of weaving, was apt to be regarded as part of the same operation rather than as a distinct art … Soph. probably had in mind η 96 πέπλοι | λεπτοὶ ἐΰννητοι βεβλήατο, ἔργα γυναικῶν' (cloth spread on the seats in the banqueting hall of the Phaeacian king Alcinous). Lloyd-Jones accordingly translates the fragment 'to weave robes and tunics made of linen'.